2008
DOI: 10.1007/s10620-008-0430-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin Treatment on HuC/HuD, NADH Diaphorase, and nNOS-Positive Myoenteric Neurons of the Duodenum of Adult Rats with Acute Diabetes

Abstract: We carried out this investigation with the purpose of verifying whether insulin treatment prevents changes in the density of myoenteric neurons of the duodenum of Wistar rats with streptozotocin short-term diabetes. The animals from the diabetic group (D) lost more weight than the controls (group C), while the insulin treatment (group T) prevented weight loss in three animals and increased visceral fat in all of the animals of this group. Insulin treatment did not prevent the early loss of HuC/HuD myoenteric n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(52 reference statements)
0
15
0
1
Order By: Relevance
“…RENATA V.F. PEREIRA, DAVID R. LINDEN, MARCÍLIO H. MIRANDA-NETO and JACQUELINE N. ZANONI Previous studies from our laboratory showed that the number of nNOS-IR neurons present per unit area does not change with diabetes in the stomach (Fregonesi et al 2005), duodenum (de Mello et al 2009), jejunum (Tronchini et al 2012) and ileum (Pereira et al 2008, Zanoni et al 2003. In the present study, when nNOS neurons were quantified per ganglion, which was not completed in the previous studies, a significantly 24.5% reduction induced by diabetes was found.…”
Section: Discussionmentioning
confidence: 91%
“…RENATA V.F. PEREIRA, DAVID R. LINDEN, MARCÍLIO H. MIRANDA-NETO and JACQUELINE N. ZANONI Previous studies from our laboratory showed that the number of nNOS-IR neurons present per unit area does not change with diabetes in the stomach (Fregonesi et al 2005), duodenum (de Mello et al 2009), jejunum (Tronchini et al 2012) and ileum (Pereira et al 2008, Zanoni et al 2003. In the present study, when nNOS neurons were quantified per ganglion, which was not completed in the previous studies, a significantly 24.5% reduction induced by diabetes was found.…”
Section: Discussionmentioning
confidence: 91%
“…Similar results were found by Pereira et al (22) in the ileum of rats using the same experimental model. Other studies did not find significant results with regard to the number of nNOS-immunoreactive neurons in different segments of the gastrointestinal tract, such as stomach (14) , distal colon (44) , and duodenum (13) . According to Pereira et al (22) , this subpopulation of neurons is highly resistant to the action of free radicals produced by DM-induced hyperglycemia, explaining the results described above, including our study of enteric neurons.…”
Section: Discussionmentioning
confidence: 78%
“…Izbeki et al [496] also found that in the jejunum, ileum and colon of rats with streptozotocin-induced diabetes, both the total and the nitrergic neuronal cell number decreased significantly, while in the duodenum only the number of nitrergic neurons decreased. De Mello et al [495] also demonstrated a significant reduction in density of the duodenal myenteric neurons stained with HuC/HuD compared with controls (18.6 and 19.77%, respectively, p<0.001). The density of nNOS neurons was also lower than that of controls (8.62 and 7.30%, respectively), but the difference did not attain statistical significance, which may suggest that the nitrergic neurons are less sensitive to acute diabetes induced by streptozotocin [495].…”
Section: Gt Segment Motility Disorders Referencesmentioning
confidence: 85%